A history of western music - Grout, Donald Jay 1902-1987.; Burkholder, J. Peter (James Peter).; Palisca, Claude V. (New York Norton, 2010)
"The narrative of A History of Western Music naturally focuses on the musical works, styles, genres and ideas that have proven most influential, enduring and significant - but it also encompasses a wide range of music, from religious to secular, from serious to humorous, from art music to popular music, and from Europe to the Americas."--Publisher's description.
Maps -- Guide to recordings -- Part one, The ancient and medieval worlds. Music in antiquity ; The Christian Church in the first millennium ; Roman liturgy and chant ; Song and dance music in the Middle Ages ; Polyphony through the thirteenth century ; French and Italian music in the fourteenth century -- Part two, The Renaissance. Music and the Renaissance ; England and Burgundy in the fifteenth century ; Franco-Flemish composers, 1450-1520 ; Sacred music in the era of the Reformation ; Madrigal and secular song in the sixteenth century ; The rise of instrumental music -- Part three, The seventeenth century. New styles in the seventeenth century ; The invention of opera ; Music for chamber and church in the early seventeenth century ; France, England, Spain and the New World in the seventeenth century ; Italy and Germany in the late seventeenth century -- Part four, The eighteenth century. The early eighteenth century in Italy and France ; German composers of the late Baroque ; Musical taste and style in the Enlightenment ; Opera and vocal music in the early classic period ; Instrumental music : sonata, symphony, and concerto at midcentury ; Classical music in the late eighteenth century -- Part five, The nineteenth century. Revolution and change ; The Romantic generation : song and piano music ; Romanticism in classic forms : orchestral, chamber, and choral music ; Romantic opera and musical theater to midcentury ; Opera and musical theater in the later nineteenth century ; Late Romanticism in Germany and Austria ; Diverging traditions in the later nineteenth century -- Part six, The twentieth century and after. The early twentieth century ; Modernism and the classical tradition ; Between the World Wars : jazz and popular music ; Between the World Wars : the classical tradition ; Postwar crosscurrents ; Music since 1970 -- Glossary -- For further reading.
Keywords: Music -- History and criticism